Systemic immune responses after ischemic stroke: From the center to the periphery - Wu, Fan; Liu, Zongchi; Zhou, Lihui; Ye, Di; Zhu, Yu; Huang, Kaiyuan; Weng, Yuxiang; Xiong, Xiaoxing; Zhan, Renya; Shen, Jian (Frontiers in Immunology, 2022)
Ischemic stroke is a leading cause of disability and death. It imposes a heavy economic burden on individuals, families and society. The mortality rate of ischemic stroke has decreased with the help of thrombolytic drug therapy and intravascular intervention. However, the nerve damage caused by ischemia-reperfusion is long-lasting and followed by multiple organ dysfunction. In this process, the immune responses manifested by systemic inflammatory responses play an important role. It begins with neuroinflammation following ischemic stroke. The large number of inflammatory cells released after activation of immune cells in the lesion area, along with the deactivated neuroendocrine and autonomic nervous systems, link the center with the periphery. With the activation of systemic immunity and the emergence of immunosuppression, peripheral organs become the second “battlefield” of the immune response after ischemic stroke and gradually become dysfunctional and lead to an adverse prognosis. The purpose of this review was to describe the systemic immune responses after ischemic stroke. We hope to provide new ideas for future research and clinical treatments to improve patient outcomes and quality of life.